Association of biochemical indicators with multimorbidity in 19,624 older adult individuals with chronic diseases: a study from Jindong District, Jinhua City, China - Yao, Qihuan; Chen, Guozhong (Frontiers in Public Health, 2025)
BackgroundChronic disease multimorbidity is influenced by multiple factors, but with little knowledge on the impact of biochemical indicators. This study aims to investigate the prevalence of multimorbidity of chronic diseases among older adult individuals in the community, as well as the factors related to biochemical indicators associated with chronic disease multimorbidity.MethodsThe study included 19,624 older adult individuals aged 60 and above in Jindong District, Jinhua City, Zhejiang Province, China. Participants completed a national standardized older adult health examination in the community. Chi-square tests and logistic regression were employed to evaluate the potential factors of biochemical indicators related to multimorbidity of chronic diseases.ResultsThe multimorbidity rate of chronic diseases in older adult patients is 70.3%. Each chronic disease coexists with one or more other chronic diseases in over 75% of cases. Among the biochemical indicators, hemoglobin (Hb) (OR = 1.46, 95%CI: 1.13–1.90), white blood cell count (WBC) (OR = 1.25, 95%CI: 1.02–1.54), red blood cell count (RBC) (OR = 1.36, 95%CI: 1.10–1.69), urinary protein (U-PRO) (OR = 1.10, 95%CI: 1.02–1.19), urinary glucose (U-GLU) (OR = 1.44, 95%CI: 1.23–1.67), alanine aminotransferase (ALT) (OR = 1.71, 95%CI: 1.39–2.10), aspartate aminotransferase (AST) (OR = 1.22, 95%CI: 1.05–1.41), creatinine (Cr) (OR = 1.28, 95%CI: 1.16–1.42), uric acid (UA) (OR = 1.36, 95%CI: 1.22–1.51), total cholesterol (TC) (OR = 1.76, 95%CI: 1.59–1.95), triglycerides (TG) (OR = 2.63, 95%CI: 2.46–2.82), low-density lipoprotein cholesterol (LDL-C) (OR = 1.84, 95%CI: 1.60–2.11), high-density lipoprotein cholesterol (HDL-C) (OR = 10.99, 95%CI: 8.12–14.90), and fasting blood glucose (FBG) (OR = 1.89, 95%CI: 1.74–2.05) are associated with the risk of multimorbidity of chronic diseases (p < 0.05). Among these, lipid parameters demonstrated the strongest associations with multimorbidity risk, with low HDL-C showing an 11-fold increase and elevated TG a 2.63-fold increase.ConclusionThis study found that the prevalence of multimorbidity among older adult individuals in this region reached 70.3%. Multiple biochemical indicators were significantly associated with multimorbidity, particularly lipid parameters (low HDL-C and elevated TG), glucose parameters (elevated FBG and positive U-GLU), liver function (elevated ALT), and hemoglobin levels. These findings provide important evidence for research on factors associated with multimorbidity in the older adult population.